Upaya Preventif dan Promosi Dalam Rangka Peningkatan Kesadaran Masyarakat Kelurahan Grogol Terhadap Bahaya Hipertrigliseridemia - Widjaja, Yoanita; Santoso, Alexander Halim; Gunaidi, Farell Christian; Kadang, Fidelis Samudra; Ramadhani, Kenzie Rafif (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Hypertriglyceridemia is an increase in triglyceride (TG) levels in the blood above normal limits, which is often associated with metabolic diseases. High triglyceride levels can disrupt lipid metabolism, causing an increase in atherogenic lipoproteins. This can increase the risk of diseases, such as atherosclerosis and acute pancreatitis. The community service program (PKM) in Grogol was implemented with the aim of increasing awareness of the productive age community regarding the importance of early detection of dyslipidemia through lipid profile screening activities, especially blood triglyceride levels. The target of the activity is productive age people because they are more exposed to the risk factors for hypertriglyceridemia. This activity uses the Plan-Do-Check-Act (PDCA) approach which includes lipid profile examinations and interactive education about risk factors and prevention strategies for hypertriglyceridemia. Of the 71 participants, it was found that 47 people (66.2%) had triglyceride levels that exceeded the normal threshold, while 24 people (33.8%) had levels within the normal range. These results emphasize the importance of routine examinations and ongoing counseling to reduce the risk of cardiometabolic complications and improve the overall quality of life of the community.